1982
DOI: 10.1063/1.442712
|View full text |Cite
|
Sign up to set email alerts
|

On the role of attractive forces in the cage effect in simple liquids

Abstract: Molecular dynamics calculations were performed in an attempt to characterize the mechanism by which attractive forces affect the velocity correlation function in simple Lennard-Jones liquids. The relationships between the presence of attractive forces, the rigidity of molecular cages, and the decay of velocity correlations were studied by molecular dynamics runs in which a single mobile particle moved in a rigid cage environment. Our results suggest that the principal role of the attractive forces is to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The different values found for the two models in the high-temperature regime reflect the fact that attractive forces already play an important quantitative role in this regime, despite the very little changes observed in static quantities. This effect was reported before in the case of simple liquids [20][21][22]. The role of attractive forces at high temperatures is partially captured by our MCT calculations, since we find theoretically a 25 % change in E ∞ between the two models.…”
Section: B Relaxation Timessupporting
confidence: 85%
“…The different values found for the two models in the high-temperature regime reflect the fact that attractive forces already play an important quantitative role in this regime, despite the very little changes observed in static quantities. This effect was reported before in the case of simple liquids [20][21][22]. The role of attractive forces at high temperatures is partially captured by our MCT calculations, since we find theoretically a 25 % change in E ∞ between the two models.…”
Section: B Relaxation Timessupporting
confidence: 85%
“…The difference between the liquid in the presence and in the absence of the attractive tail is small but already noticeable at high temperature in the "normal" range (see also Refs. [8,9]) and it rapidly builds up in the low-temperature regime relevant for the glass transition phenomenon [10]. Here, we analyze in more detail the influence of the density.…”
Section: B Dynamic Correlations and Timescalesmentioning
confidence: 99%
“…If the van der Waals picture and the WCA theory of liquids have been extensively studied and tested as far as the pair structure and the thermodynamics are concerned, much less has been undertaken for the dynamics. Actually, the WCA theory and the associated division of the pair potential have not been submitted to systematic investigations [8,9]. We have recently revisited this point in the context of glass formation and found that a binary Lennard-Jones model and its WCA reduction to the repulsive components of the pair potentials, when studied at the same density, show very similar static pair density correlation functions but widely differing relaxation times as one lowers the temperature towards the glass phase [10].…”
Section: Introductionmentioning
confidence: 99%
“…The so-called ''van der Waals picture of liquids'' [2,3], i.e., the predominance of the short-ranged repulsive part of the intermolecular potentials in determining the structure of dense nonassociated liquids, has proved very fruitful for predicting the pair correlation functions and the thermodynamics. Although not as thoroughly tested [4][5][6][7][8], it has been useful for the dynamics as well [9].More recently, this picture, in which the attractive part of the interactions is treated as a mere cohesive background amenable to perturbative treatment, has been transposed to the viscous (supercooled) liquid regime. A number of approaches either suggest or take for granted that the structure and the dynamics of viscous glass-forming liquids are controlled by the short-ranged repulsive forces.…”
mentioning
confidence: 99%
“…The so-called ''van der Waals picture of liquids'' [2,3], i.e., the predominance of the short-ranged repulsive part of the intermolecular potentials in determining the structure of dense nonassociated liquids, has proved very fruitful for predicting the pair correlation functions and the thermodynamics. Although not as thoroughly tested [4][5][6][7][8], it has been useful for the dynamics as well [9].…”
mentioning
confidence: 99%